Not Thanks to But Despite: Why the Russian Economy Is Not Yet Bad Enough. Issue 4 (3rd July 2016) - Aleksashenko, Sergei
Abstract : Although the Russian economy declined in 2015, the decline was not as serious as expected by Russian leaders. None of the disasters anticipated at the end of 2014 happened. The decline was moderated by continued demand from the main consumers of Russian raw materials, continued government financial support for the defense industry, and balancing changes in internal prices. The ruble has remained stable because it is largely dependent on the price of oil on world markets. The impact of Western sanctions on the Russian economy steadily declined throughout 2015. Although Russia avoided economic collapse, the prospect for the near future is continued stagnation, rather than renewed growth.